Effect of Two Different Drying Techniques on the Chemical Composition of Amaranthus - Udoh, Mary Athanasius; Yahaya, Musbau Adekunle; Olayemi, Abimbola Gbenga; Ijezie, Augustina Elochukwu; Dambazau, Zainab Bello; Ngwu, Faith Amarachi (Darul Yasin Al Sys, 2025)
Amaranth (Amaranthus), a widely consumed green leafy vegetable in Nigeria, is valued for its rich content of micronutrients, macronutrients, phytonutrients, and potential food-toxicants. This study evaluates the impact of two common drying methods—sun-drying and oven-drying—on the chemical composition of Amaranthus leaves. A total of 2.5 kg of fresh Amaranthus leaves was procured from Watt Market in Calabar, Cross River State, Nigeria. After stalk removal, the leaves were divided into three equal portions: one left untreated as control, while the others were subjected to sun-drying and oven-drying for one month. The dried samples were pulverized, packaged in airtight containers, and stored under cool, dry conditions prior to analysis. Proximate composition, mineral content, and phytochemical screening were conducted using standard analytical techniques. Results indicated a significant reduction in moisture content from 84.30 ± 0.1% in the fresh sample to 23.70 ± 0.1% (sun-dried) and 11.30 ± 0.1% (oven-dried), thereby increasing dry matter availability. Concentrations of ash, fibre, crude fat, crude protein, and carbohydrates were elevated in the dried samples due to moisture loss. However, notable reductions in mineral content were observed—Calcium (Ca) declined from 2.78 mg/100g in the control to 2.10 mg/100g (sun-dried) and 1.07 mg/100g (oven-dried). Heat treatment also led to a significant decrease in anti-nutrients and food-toxicants, with oven-drying showing greater efficacy. The study concludes that both sun-drying and oven-drying effectively preserve Amaranthus leaves, though with some loss of micronutrients. Consuming larger quantities of the dried vegetable may help offset these losses, providing essential nutrients for populations at risk of malnutrition.